Pengembangan Media Tas Papan Flanel untuk Kemampuan Bahasa Ekspresif Anak Usia Dini - Chodijah, Siti; Nugroho, Aryo Andri; Purnamasari, Iin (Universitas PGRI Semarang, 2022)
This study aims to determine: (1) the need for learning media for Early Childhood Educators (PAUD) in improving language skills in early childhood. (2) Learning Media Development Procedures that are suitable for use in improving early childhood language skills. (3) The implementation of the use of Learning Media using flannel board bags in improving expressive language skills in early childhood. This research method uses the development model developed by Borg Gall. Brog and Gall argues that the Research and Development (RD) approach in education includes ten steps. The main purpose of this research and development method is used to produce products and determine the feasibility of the products developed in the form of flannel board bags. Data collection techniques used interviews, FGD (Focus Group Discussion), observation and validation questionnaires from material experts and media experts. Data analysis technique using validity test, reliability test, effectiveness test, practicality test, descriptive statistical analysis, and Wilcoxon Signed Ranks Test. The conclusion is that learning with flannel board bags can improve expressive language skills in early childhood.Â